Desain Dan Validasi Materi Ajar Mitigasi Bencana Berbasis Web Game: Studi Pengembangan pada Siswa SMA di Kota Bengkulu - Muhammad Alfi; Mirna Yunita; zairin (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
The high risk of earthquakes and tsunamis in Bengkulu City has not been matched by adequate literacy and preparedness among high school students. Conventional learning materials are considered uninteresting and ineffective in instilling practical skills, creating a gap between knowledge and preparedness. This study aims to (1) design and develop disaster mitigation teaching materials in the form of contextual web games, (2) test the validity and practicality of the product, and (3) evaluate its effectiveness in increasing students' knowledge and motivation to learn. This development research uses the 4D model 4D (Define, Design, Development, Disseminate). The test subjects consisted of experts (in materials, media, and learning), 3 teachers, and 35 11th grade high school students in Bengkulu City. Data were collected through expert validation sheets, teacher and student response questionnaires, knowledge tests (pre-test/post-test), and the Game Experience Questionnaire (GEQ). The expert validation results showed that the product obtained an average score of 4.42 (scale of 5) in terms of material, media, and graphics, with a category of “highly valid”. Teacher and student responses to practicality reached 89% and 87% with a category of “very practical.” The effectiveness test results showed a significant increase in knowledge (N-Gain 0.71, high category) and student learning motivation (GEQ score 3.9/5) in the immersive and positively challenging categories. The conclusion of this study is that the web-based game teaching material developed has met the criteria of validity, practicality, and effectiveness in improving knowledge and learning motivation in disaster mitigation. The implication is that this product can be recommended as an innovative learning medium to support the Disaster Preparedness School program in disaster-prone areas. Translated with DeepL.com (free version).